Staphylococcal Chromosomal Cassette Type in Clinical Strains of Methicillin-Resistant Staphylococcus aureus - Maribel J. Castellano González; María E Cavazza Porro; Armindo J Perozo Mena (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2014)
Methicillin-resistant Staphylococcus aureus (MRSA) presents a protein that binds to penicillin, the PBP2a, encoded by the gene mecA, located in a mobile genetic element called the staphylococcal chromosomal cassette (SCCmec). This study was conducted to examine the antimicrobial susceptibility, Panton-Valentine leukocydine (PVL) production and the staphylococcal chromosomal cassette mec (SCCmec) type for MRSA isolates from 54 patients in a hospital during a three-month period. Antimicrobial susceptibility testing was performed using an agar diffusion method; mecA, PVL and SCCmec types were determined using polymerase chain reaction (PCR). Twenty-nine strains (29) corresponded to type IV SCCmec (54%), 22 to type I SCCmec (40%), 2 to type IA SCCmec (4%) and 1 to SCCmec IIIB (2%). Nineteen strains (35%) were positive for PVL, all of type IV SCCmec. Forty strains (74%) expressed multiresistance. All MRSA isolates were susceptible to vancomycin, teicoplanin, linezolid, tygecicline and moxifloxacina. No statistically significant association was found between the presence of the PVL gene, antimicrobial resistance and the SCCmec type (p>0.05). SCCmec types IV and I are the most frequent in the MRSA strains circulating in the institution.